Effect of science in the relation between firms' technological diversification and innovation performance - Donato, Alessia (Journal of Mathematical Economics and Finance; Vol 6 No 1 (2020): JMEF, Volume VI, Issue 1(10), Summer 2020DO - 10.14505/jmef.v6.1(10).01, 2020)
Several studies have analyzed the relationship between the firms’ technological diversification and the innovation performance outcomes. We use information coming from patents portfolio of a sample of firms that operate in a nanotechnology sector and analyze the effect, in this relationship, of the use of scientific knowledge in the development of patented inventions. We find, firstly, that the trend of the quality of innovation with the technological diversification of a firm appears similar to a Gaussian with positive asymmetry. Secondly, we find that with the increase in the percentage of the used science by year, in one side, firms appear to obtain the maximum impact of the innovation, in average, with a less technological diversification in the patent’s portfolio and, in the other side, innovations with more impact are obtained in average.